P3 α7 nicotinic acetylcholine receptor expression in vascular cells during normoxia and hypoxia. (May 2019) - McLoughlin, Wesley KX; Lucatelli, Christophe; Peters, Dan; Baker, Andrew H; Newby, David E; Hadoke, Patrick; Tavares, Adriana AS; MacAskill, Mark G
Abstract : Introduction: The α7 nicotinic acetylcholine receptor (α7nAChR) has been previously shown to have an essential role in angiogenesis 1 . A number of positron emission tomography (PET) radiotracers, such as 18 F-NS14490 2, are now available for the non-invasive imaging of α7nAChR. This highly sensitive imaging approach has the potential to be a powerful tool to study the angiogenic process in a number of pathologies. However, as part of the validation of this target for angiogenesis, a better understanding of the α7nAChR in vascular cells under angiogenic conditions is needed. Objective: This study aims to investigate the in vitro expression of α7nAChR in human vascular-associated cells under angiogenic conditions in order to evaluate its suitability as a marker for angiogenesis. Methods: Various human cell types were cultured, Human Umbilical Vein Endothelial cells (HUVEC), THP-1 derived Macrophages (PMA stimulated for 72 hour), Human Cardiac Microvascular Endothelial cells (CMVEC), Human Coronary Artery Smooth Muscle cells (CVSMC). Sub-confluent cultures were exposed to hypoxia (1% O2 ) over a time course (0–16 hours). The protein content of lysed cells was quantified by spectrophotometry before western blotting was carried out to assess α7nAChR expression relative to GAPDH using the Licor system of detection. α7nAChR expression was assessed in the treatment groups vs. a basal control, which for endothelial and smooth muscle cells was normoxic, non-proliferating confluent cultures, and for the macrophage was a normoxic culture. Results: HUVEC demonstrated a significant increase in α7nAChR expression under proliferation and hypoxia, with α7nAChR expression peaking at 2 hours post hypoxia (p<0.005 Kruskal-Wallis with post-hoc Dunn's vs Basal). A similar trend was seen in the CMVEC, showing the highest expression at 2 hour post hypoxia, although this did not reach statistical significance. The macrophages showed the highest α7nAChR expression compared to the other cell types, but had no hypoxia-driven response. CVSMC had the lowest expression of α7nAChR in the cell types tested, and displayed no hypoxia-driven change in response. Conclusion: This study demonstrates that all investigated cells expressed α7nAChR, with the highest expression found in macrophages, followed by endothelial cells, and then CVSMC. Importantly, only the endothelial cells exhibited a hypoxia-driven increase in α7nAChR expression. The results of this study suggest that α7nAChR may be a useful marker of angiogenesis, warranting further investigation. References: Heeschen, C. et al. (2002). J Clin Investig. 110(4):527–536. Rötering, S. et al. (2013). Bioorganic Med Chem. 21(9):2635–2642.